Navigating Cohesion in Canon Law: Uniformity, Plurality and the Multi-Source Legal Order - Michowicz, Przemysław (Prawo Kanoniczne, 2026)
The problem addressed: Canon law operates within a framework of normative multicentrism, understood as the coexistence of multiple law-making and law-applying authorities in the Church, including universal and particular legislators, bishops’ conferences, the Magisterium, and the reception of secular norms (notably European Union data protection law). This situation raises fundamental questions about the meaning and scope of legal uniformity in the canonical order. The aim of the research conducted: The article aims to demonstrate that uniformity in canon law is not an absolute or purely formal value, but a functional and relational category. It serves legal certainty, equality of the faithful, and the preservation of a shared ecclesial axiology and teleology, especially the principle of salus animarum. Methods: The study employs doctrinal, historical, and comparative methods. It reconstructs the development of the canonical legal order from early normative pluralism to modern codification and analyzes the relationships between various normative centers. The results of the research: The analysis shows that multicentrism is an immanent and structurally inherent feature of canon law. Uniformity does not imply identity of norms or practices, but a dynamic process of interpretative integration grounded in common values. The conclusions drawn from the research: The concept of a “canonical legal order” more accurately describes canon law than that of a strictly uniform legal system, as it captures unity through functional coherence rather than formal homogeneity.